Saddle versus non-saddle pulmonary embolism: differences in the clinical, echocardiographic, and outcome characteristics. Issue 1 (31st December 2022) - Ibrahim, Wanis H; Al-Shokri, Shaikha D; Hussein, Musa S; Kamel, Antoun; Abu Afifeh, Lana M; Karuppasamy, Gowri; Parambil, Jessiya V; Elasad, Farras M; Abdelghani, Mohamed S; Abdellah, Ahmed; Faris, Mohammed E
ABSTRACT: The central location, the size, and instability of saddle pulmonary embolism (PE) have raised considerable concerns regarding its hemodynamic consequences and the optimal management approach. Sparse and conflicting reports have addressed these concerns in the past. We aimed to evaluate the clinical presentation, hemodynamic and echocardiographic effects, as well as the outcomes of saddle PE, and compare the results with those of non-saddle type. This was a retrospective study of 432 adult patients with saddle and non-saddle PE. Overall, 432 patients were diagnosed with PE by computed tomography pulmonary angiography (CTPA). Seventy-three (16.9%) had saddle PE, and 359 had non-saddle PE. Compared to those with non-saddle PE, patients with saddle PE presented more frequently with tachycardia (68.5% vs. 46.2%, P = .001), and tachypnea (58.9% vs. 42.1%, P = .009) on admission, required more frequent intensive care unit (ICU) admissions (45.8% vs. 26.6%, P = .001) and thrombolysis/thrombectomy use (19.1% vs. 6.7%, P = .001), and were at more risk of developing decompensation and cardiac arrest after their initial admission (15.3% vs. 5.9%, P = .006). On echocardiography, right ventricular (RV) enlargement (60% vs. 31.1%, P = .000), RV dysfunction (45.8% vs. 22%, P = .000), and RV systolic pressure (RVSP) of greater than 40 mmHg (61.5% vs. 39.2%, P = .003) were significantly more observed with saddle PE. The two groups did not differ concerning the rates of hypotension (17.8% vs. 18.7%, P = .864) and hypoxemia (41.1% vs. 34.3%, P = .336) on admission and mortality rates. A logistic regression model indicated that the use of oral contraceptive pills (OCP), RVSP > 40 mmHg, and development of hypotension and decompensation following admission were associated with an increased likelihood of having saddle embolus. Saddle PE accounts for a higher proportion among all PE cases than previously reported. Patients with saddle PE tend to present more frequently with adverse hemodynamic and echocardiographic changes and decompensate after their initial presentation. OCP use, development of hypotension, and decompensation following admission and RVSP > 40 mmHg are significant predictors of saddle PE. These characteristics should not be overlooked when managing patients with saddle PE.